Personality as a Key Factor in Financial Management of Traditional Market Traders: Kepribadian sebagai Faktor Utama dalam Manajemen Keuangan Pedagang Pasar Tradisional - Qoni’ah, Nanda Sayyidah; Rahmawati, Imelda Dian (Indonesian Journal of Law and Economics Review, 2024)
Financial management behavior is crucial for the success of small traders, particularly in traditional markets. In Indonesia, traditional market traders often face challenges in managing their finances effectively due to varying levels of financial literacy, attitudes, and personality traits. Limited research has examined how these factors specifically affect financial management behavior in traditional market settings. This study investigates the relationship between financial literacy, financial attitudes, and personality with the financial management behavior of traders in three major markets in Sidoarjo: Larangan, Porong, and Gedangan. Utilizing primary data from 100 respondents through random sampling and analyzed using SPSS, the findings reveal that financial literacy and attitudes do not significantly influence financial management behavior. However, personality shows a positive and significant effect on financial management behavior among these traders. This study uniquely highlights personality as a key factor in financial management, suggesting that individual traits may outweigh financial knowledge or attitudes in this context. The results emphasize the need for financial education programs to consider personality traits, enhancing financial management practices among traditional market traders. Highlights: Personality significantly impacts financial management behavior among traditional market traders. Financial literacy and attitudes do not directly influence financial management in this context. Financial education should incorporate personality traits to improve management practices. Keywords: Financial Literacy, Personality, Financial Attitude, Market Traders, Financial Behavior